The forger's spell : a true story of Vermeer, Nazis, and the greatest art hoax of the twentieth century - Dolnick, Edward (HarperCollins, 2008)
As riveting as a World War II thriller, The Forger's Spell is the true story of Johannes Vermeer and the small-time Dutch painter, Han van Meegeren, who dared to impersonate Vermeer centuries later. The con man's mark was Hermann Goering, one of the most reviled leaders of Nazi Germany and a fanatic collector of art